Selected Aspects of Asset Deals under South African and Swiss Law - Kocher, Sarah (Department of Commercial Law, 2014)
Although there are many methods to accomplish reorganisations, and these methods may be used in combination, there are broadly speaking two categories of such transactions. First, two or more companies may merge. At least one of the merging companies is dissolved and both of the undertakings form part either of a newly formed company, or of the merging company, which does not cease to exist. Second, an undertaking may be purchased. There are two methods to achieve this: control over a company can be established by a takeover of its undertaking ('asset deal') or by obtaining enough shares in a company to control it in general meeting ('share deal'). Unlike share deals and mergers, asset deals do not remodel or vary membership rights. When referring to an 'undertaking' my intention is to refer to the company's enterprise as such in all its components. As of today there are no comprehensive provisions in the South African Companies Act ('CA')1 that regulate the transfer of assets and liabilities in a pure asset deal. The only provision referring to asset deals is s 228 CA. Said section is mainly concerned with the authority of directors to dispose of assets or part of an undertaking where such transactions are of a certain size. Further, s 197 of the Labour Relations Act2 and s 34 of the Insolvency Act3 may apply if a company alienates business assets. With the coming into effect of the Swiss Merger Act ('SMA')4 on July 1 2004, a new mechanism for 'the transfer of assets and liabilities' respectively the transfer of a company's undertakings was created. It applies to any entity or person registered in the Commercial Registry. 5 The major advantage of this new instrument is that all assets and liabilities are transferred to the transferee by operation of law upon registration of said transaction with the I will conclude with a comparison of the transfer of assets and liabilities under the SMA and under s 313 CA. The latter provision deals with reconstructions and amalgamations and involves rearrangement of membership rights as such it is beyond the scope of pure asset deals. Nevertheless, the comparison is an interesting one, especially as the prospective Companies Bill, 20078 seems to adopt a similar model to implement pure asset deals.